"We bounce back from the worst of the worst": assets of Flint-area women identified in the Flint Women's Study. Issue 1 (2nd January 2023) - Hailemariam, Maji; Bustos, Tatiana; Felton, Julia; Key, Kent; Greer, DeOnica; Jefferson, Bernadel L; Muhammud, Janice; Robinson, Dewaun; Saddler, Sharon; Spencer, Bryan; Miller, Raven; Richie, Fallon; et al.
ABSTRACT: Economically disadvantaged communities experience disproportionate health and social challenges relative to more affluent areas. This study describes ways women support and give back to their community in a minority-majority community experiencing social, economic and health challenges. We conducted qualitative interviews with 100 women and human service providers serving women in Flint, Genesee County, Michigan. Using methods aligned with community-based participatory research, a group of community and academic partners analyzed the data. Participants noted several personal characteristics of women they identified as assets including resilience, strength, resourcefulness, creativity, determination, tenacity, wisdom and the ability to nurture others. We think these personal characteristics represent individual assets that help women in Flint survive and build social capital. Women reported developing their social capital through giving, collaborating and sharing their skills with people in their personal networks. Significant personal assets in the form of individual characteristics already exist within Flint. Even in an area characterized as having health and economic challenges, women in this study were able to leverage their personal assets to build social capital and to mobilize resources for their benefit and the benefit of the community.